النظام القانوني المستحدث لتمويل المؤسسة الناشئة في الجزائر - عبدلي حبيبة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
عمدت السلطات الجزائرية إلى خلق نموذج اقتصادي جديد بعيد عن الريع الذي تعتمده في اقتصاد البلاد منذ عقود من الزمن و ذلك بالاستثمار و دعم المؤسسات الناشئة في الجزائر من اجل المساهمة في دفع عجلة التنمية و تعزيز الإنتاج المحلي عن طريق تكريس أساليب حديثة لتمويل هذه المؤسسات باعتبارها احد ركائز التنمية الاقتصادية ، غير أن تمويلها يبقى تحديا كبيرا بين مؤسسات التمويل و المتطلبات التمويلية المستحدثة لهذه المؤسسات الناشئة كبدائل لسد الفجوة التمويلية لها و ضمان استمراريتها بتشجيع و دعم أنظمة التمويل خارج نظام القروض المصرفية و فتح مداخل جديدة للتمويل أمام هذه المؤسسات مثل شركات رأس المال المخاطر و شركات التأجير لتحسين مناخ الأعمال. و جذب الأفراد الراغبين في إنشاء مؤسساتهم ، و ضمان تسهيل الإجراءات الإدارية و توفير المعلومات لهم . The Algerian authorities have extended to create a new economic model far from the rent that they have adopted in the country’s economy for decades by investing and supporting emerging institutions in Algeria in order to contribute to advancing development and enhancing local production by devoting modern methods to financing these institutions as one of the The pillars of economic development, however, financing them remains a major challenge among the financing institutions and the financing requirements developed for these emerging institutions as alternatives to bridge the financing gap for them and ensure their continuity by encouraging and supporting financing systems outside the bank loan system and opening new entrances for financing to these institutions such as venture capital companies and leasing companies to improve the business climate.